Adequate and quality prenatal care among pregnant women in a lima hospital: prevalence and associated factors - Brito Hijar, Andrea Denise (2025)
Objective: To determine the prevalence of adequate and high-quality prenatal care and to identify associated sociodemographic and obstetric factors among pregnant women attended at a public hospital in Lima during 2023. Methods: An observational, analytical, and cross-sectional study was conducted with 388 pregnant women who gave birth at Hospital I Octavio Mongrut Muñoz between February and December 2023. Chi-square tests and binary logistic regression were used to estimate crude and adjusted prevalence ratios (PRs) with 95% confidence intervals (95% CI). Results: A total of 40.5% received adequate prenatal care and 7.8% received high-quality care. Being married was positively associated with adequate care (adjusted PR=2.49; 95% CI: 1.02–6.11; p=0.045), while having one living child decreased the probability (adjusted PR=0.47; 95% CI: 0.24–0.94; p=0.031). High-quality care was associated with receiving care at referral centers (adjusted PR=2.68; 95% CI: 1.04–6.90; p=0.041) and being initially attended by a midwife (adjusted PR=0.12; 95% CI: 0.03–0.55; p=0.006). Conclusion: Prenatal care coverage and quality were limited. Individual factors (marital status, parity) and system-level factors (type of facility, provider) significantly influenced care, highlighting the need for targeted interventions to reduce maternal health inequities.